Uma análise do mercado da erva-mate produzida no Brasil, 2000-2020 - Oliveira, Twanny Emmanuelly Gomes de (2022)
Yerba Mate is a species of subtropical perennial plant from South America. Its presence is remarkable in countries such as: Brazil, Argentina, Paraguay, Bolivia and Chile, and the first three countries are the largest producers and exporters. world. Historically, Yerba Mate is consumed in the form of an infusion in various cultures as a social habit and culture, but the purposes of its application have expanded every year, being already used in the production of cosmetics, personal hygiene products, soft drinks and carbonated drinks. caffeine based. Considering the importance of this raw material for the Brazilian economy, this research sought to analyze the productive and exporting evolution of Brazil of mateculture, over the years 2000 to 2020. For this, the work made use of two different instruments, the Exploratory Analysis of Spatial Data and the Constant Market Share model. The first allowed analyzing the average productivity of producing municipalities between the years 2001 to 2019 and the second, the estimation of the Brazilian market shares and their sources of growth over the period from 2001 to 2020. The results show a good performance of the country regarding both fronts, however, they still indicate the need for improvements in the incentive to production and research for the development of new products, as well as the creation of more consistent strategies of international trade for the sector.